LABORATORY STUDIES IN OBSTETRICS, GYNECOLOGY AND NEONATOLOGY - Bazarova Minura Usmanovna; Gafurova Shaxnoza Mavlyanovna (Scholar Express Journals, 2022)
The state of vaginal biocenosis has a serious impact on the reproductive function and, as a consequence, on the quality of life of a woman. Classical clinical and laboratory methods of examination of women in gynecology are cultural and microscopic (examination of a gynecological smear), but they are not always effective enough. Recently, molecular genetic methods for assessing vaginal biocenosis (PCR) have been introduced into clinical diagnostic laboratories, however, their use for screening purposes is not always possible, since they are not included in the standard list of studies and are often paid for at the expense of patients' own funds
Keywords: Pathological Discharge; Endothelium And Angiogenic Factors; Laboratory Diagnostics